Of Mice and Men play still - Peter Stackpole:::Creator::::::::::::
In this Of Mice and Men play still of a Broadway theater production, Curley's wife (Clare Luce) is grabbed by Lennie (Broderick Crawford). This performance took place on the 'Barn Stage.'. RESTRICTED USE. The originals are in the safe (2 copies).